Levels and Patterns of Safety Net Spending in Developing and Transition Countries - Andrews, Colin (World Bank, Washington, DC, 2012)
This paper offers a new set of data compiled from individual World Bank country reports and covering 87 developing and transition countries during 1996-2006. The findings show that mean spending on safety nets is 1.9 percent of gross domestic product (GDP) and median spending is 1.4 percent of GDP across developing and transition countries. For about half of these countries, spending falls between 1 and 2 percent of GDP. Some variation is apparent. Bosnia and Herzegovina, Pakistan, and Tajikistan, for example, spend considerably less than 1 percent of GDP, while spending on social safety nets in Ethiopia and Malawi is nearly 4.5 percent of GDP because international aid is counted, but would be more like 0.5 percent if only domestically financed spending were counted. Other high-spending countries, Mauritius, South Africa, and the Slovak Republic, finance their safety nets domestically. Spending on safety nets is less variable than spending on social protection or the social sectors.